Rainwater Harvesting in the Rainforest: A Technical and Socioeconomic Review of Community Approaches in Brazil. Issue 1 (October 2021) - Farrell, Amy; Swan, Dr Andrew; R. Mendes, Dr Ronaldo Lopes
Abstract: This paper reviews potable water issues affecting river dwelling communities and assesses the use of Rainwater Harvesting techniques to help meet potable water requirements. The study specifically explores river communities on the periphery of the city of Belem, where there is no potable mains water supply. This interdisciplinary study reviews the socioeconomic context of the different organisational stakeholders as well as analysing technical data to ascertain the effectiveness of the systems in practice. Surveys indicate nearly half of residents consume water from sources potentially contaminated by raw sewage and mining effluent with detrimental impacts to public health. This paper reviews previous local studies and describes ongoing attempts to derive locally appropriate rainwater collection and treatment processes. This includes attempts to construct and trial organic material-based rainwater filters that comprise of different mixes of sand, gravel and activated carbon derived from by-products of local fruit processing industries, namely acai harvesting.